Cold Stamping Forming Simulation and Springback Analysis of High Strength Steel Plate for Automobile Body - Yaping Gong, Junbin Lou, Wenhong Hou, Lin Su, Shuaijun Wang, Liangxiong Dong (Forest Chemicals Review, 2022)
Springback is an inevitable physical phenomenon in cold stamping forming, which directly affects the forming accuracy and surface quality of stamping parts. When the springback exceeds the allowable error range, forming defects are formed, which brings great difficulties to mold design. Under this background, this paper analyzes the stamping forming process and springback process of high-strength steel plate based on AUTOFORM software, and discusses the influence rules of different forming processes and die parameters, including theblank holder force, die clearance and stamping speed on the forming quality of steel plateby orthogonal analysis. The springback simulation analysis is used to guide the improvement of stamping process, and the measured springback is compared and verified. The results show that the blank holder force and die clearance have the greatest influence on the thinning rate and the maximum springback value. The springback of parts can be basically controlled within 1mm, the qualified rate of parts can be improved, and the number of die trials can be reduced.